Advantages and Disadvantages of Flexible Forms of Employment in the Opinion of Employees - Wysocka, Magdalena (Olsztyn Economic Journal, 2019)
Flexibility of the labour market and employment in atypical forms has been indicated for years as a potential source of more effective competition. However, both types of flexibility constitute important changes for employees that cause concern in terms of employment security. In this con-text, the aim of the research was to determine opinions about the advantages and disadvantages of employment in atypical forms. The research was carried out in a chain of pharmacies and among paramedics, i.e. in entities where flexible employment constitutes the basic employment relation-ship. In the respondents’ opinion, there are more disadvantages than advantages of employment in flexible forms, and the main disadvantage of atypical work is employment insecurity.